Effectiveness of the Therasuit Method in the Management of Chronic Non-evolving Encephalopathy: Case Report in Pediatrics - Andrade, Thaís Alves; Antas, Bárbarah Carolyne Moreira Rodrigues; Gislainy, Géssika (Brazilian Journal of Case Reports, 2024)
Cerebral palsy (CP) is a non-progressive neurological condition that affects motor and postural ability, resulting from a static brain lesion. Early and intensive physical therapy intervention can promote significant improvements in the functionality and quality of life of affected individuals. To report the case of a girl with GMFCS level IV spastic quadriparesis, highlighting the clinical evolution and benefits of an intensive physicaltherapy approach from the first months of life. A female patient diagnosed with cerebral palsy started physiotherapy at three months of age, with an intervention plan that included sessions two to five times a week. Gross motor function was assessed using the GMFM scale, as well as qualitative analysis of videos and progress records. The patient showed significant improvements in her motor skills, including the ability to crawl, sit without support, and transfer positions independently. The patient's case report illustrates the positive impact of early and intensive physiotherapeutic intervention in children with cerebral palsy. This case underlines the importance of continued follow-up adapted to individual needs, emphasizing the capacity for neuroplasticity and the functional improvement that can be achieved, reinforcing the need for personalized and intensive treatment strategies to maximize developmental potential in patients with CP.